2016
DOI: 10.4236/jcdsa.2016.61002
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of Novel Natural Polysaccharides Sacran as a Skincare Material for Atopic Dermatitis Patients

Abstract: Atopic dermatitis is a skin disease characterized by inflammation, pruritus, and chronic or relapsing eczematous lesions. Recently, ampholytic polysaccharide sacran has attracted a particular focus of attention as a novel biomaterial. In the present study, we investigated the effect of sacran solution on atopic dermatitis in the clinical study. Almost all of the average scores for atopic dermatitis symptoms of each patient treated with sacran solutions were improved. In addition, the scores of sleep disorder a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 27 publications
(23 reference statements)
1
15
0
Order By: Relevance
“…Previously, we demonstrated that sacran solution suppressed the β-hexosaminidase release in RBL-2H3 cells, which are now known to be an analog of rat mucosal mast cells, indicating the inhibition of mast cell degranulation. 24) These results suggest that the anti-inflammatory effects of sacran may contribute to inhibition of not only prostaglandins but also other inflammatory mediators.…”
Section: Fig 6 Effects Of Sacran On Tpa-induced Skin Inflammation Imentioning
confidence: 77%
“…Previously, we demonstrated that sacran solution suppressed the β-hexosaminidase release in RBL-2H3 cells, which are now known to be an analog of rat mucosal mast cells, indicating the inhibition of mast cell degranulation. 24) These results suggest that the anti-inflammatory effects of sacran may contribute to inhibition of not only prostaglandins but also other inflammatory mediators.…”
Section: Fig 6 Effects Of Sacran On Tpa-induced Skin Inflammation Imentioning
confidence: 77%
“…In addition, previous studies regarding the physico-chemical behaviors of sacran and composites of sacran and polyols, demonstrated their unique characteristics in which sacran or the composites with polyols formed water insoluble gel-like sheets that had protective effects against chemicals and interfered with their penetration. 8) Although those results suggested that the physico-chemical properties are responsible for the improvement of skin conditions of subjects with an impaired skin barrier, the HaCaT keratinocytes were pretreated with or without 0.02% sacran for 24 h after which they were cultured with SLS at various concentrations as noted. Cell viability was measured using the neutral red assay, and is expressed as a percentage against sham-treated cells.…”
Section: Discussionmentioning
confidence: 99%
“…6) It has been reported that sacran also has a unique physical property in that it can form a gel-like film in combination with polyols and such a film can decrease the water evaporation rate and the penetration of calcein like an artificial barrier. 8) Furthermore, a serum containing sacran can improve skin conditions both in healthy subjects and in patients with AD. 9,10) Considering these facts, it is expected that sacran works not only as an artificial barrier on the skin surface but also penetrates to living epidermal cells to improve skin conditions.…”
mentioning
confidence: 99%
“…These unique characteristics were expected to provide protection to the skin against external stimuli and water evaporation. It has been reported, based on a questionnaire survey, that sacran solution reduced itching and facial rash in patients with atopic dermatitis, and that sacran inhibited the development of allergic reactions following sensitization by 2,4,6‐trinitrochlorobenzene . Although these reports described beneficial effects of sacran on diseased skin (e.g.…”
Section: Discussionmentioning
confidence: 99%